ENVIRONMENTAL CARE ATTITUDE OF THE STUDENTS IN SENIOR HIGH SCHOOL AT PATI REGENCY - Novika Adi Wibowo; Sarwono Sarwono; Yasin Yusup (Universitas Sebelas Maret (UNS), 2021)
The research aims to determine the environmental care attitude in Senior High School 1 Kayen. The research samples were the tenth-grade students, eleventh-grade students, and third-grade students of Social Science (IPS) class at Senior High School 1 Kayen. The research used Slovin formula to obtain 192 samples from the tenth grade, eleventh grade, and twelfth grade. The study used a random sampling technique. Questionnaires were used as the data collection techniques to measure knowledge about environmental care attitudes using calculation techniques of Likert scale and percentage formula. The result shows the students in Senior High have the moderate category on environmental care attitude, with a total frequency of 89 students consisting of tenth-grade students, eleventh-grade students, and twelfth-grade students in Social Science (IPS) class with a percentage score of 46,35%. In an attempt to increase students’ environmental care, we suggest several educational agents, such as Educational supervisors, Principals, and Teachers give the students examples of good actions to the environment in daily routine.